Influence of the patient’s race on the dentist’s decision to extract or retain a decayed tooth - Cabral ED, Caldas Jr AF, Cabral HAM. (Blackwell Synergy, 2005)
The aim of this study was to investigate the influence of the patient’s race on the dentist’s decision to extract or retain a decayed tooth.